Flotation kinetic models for fixed and variable pulp chemical conditions. (July 2015) - Albijanic, Boris; Subasinghe, Nimal; Park, Chul H.
Highlights: Flotation kinetic models are analysed for a wide range of reagent conditions. Flotation kinetic models are extended for variable chemical conditions. The Gamma and Kelsall model showed the best result. Abstract: This note deals with the analysis of flotation kinetic models (i.e. the Rectangular, Kelsall, first order with Dirac delta function, and Gamma model) at fixed pulp chemical conditions. It also focuses on the potential application of these models for variable pulp chemical conditions. The flotation tests were performed in a mechanically agitated batch flotation cell at a wide range of chemical conditions by varying pH, collector and activator dosage at two different P 80 values. The results showed that all flotation models, used in this study, can be applied to model variable pulp chemical conditions by introducing the power law relationship between model parameters ( R ∞ and kinetic parameters) and flotation variables (pH, collector and activator dosage). The Gamma and Kelsall model slightly better predicted flotation recovery than first order model with Dirac delta function and Rectangular model for both fixed and variable pulp chemical conditions. The flotation kinetic models for variable pulp chemical conditions might be beneficial in optimization of flotation circuits. However, this requires a significant amount of further work.